UPAYA MENINGKATKAN KEMAMPUAN MOTORIK SISWA KELAS V SDN GADING I SURABAYA MELALUI PERMAINAN TRADISIONAL - Iswardhani, Ayu Febbyastri; Saputra, Bagus Andinata; Chandra, Difa; Wahyudi, Heri; Johanis, Feri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Preserving traditional games should start from basic education. For this reason, the application of traditional games at elementary school level is very important. Not only as a conservation effort, traditional games can also be used as a method to improve elementary school students' motor skills. This research was a PTK type, with a sample of 25 class V students at SDN 1 Gading Surabaya. This research uses the traditional game of stilt batok. Data analysis in this research uses percentages. The results of cycle 1 were 9 students in the sufficient category, 2 good, 1 very poor, and 13 students in the poor category. The results of Cycle 2 were 9 students in the good category, and 16 students in the very good category. The mean results show that there was an increase between cycles 1 and 2, that in cycle 1 the percentage was 58.40% in the poor category and for cycle 2 it rose to 80.48% in the very good category. The conclusion obtained is that traditional games can improve the motor skills of fifth grade elementary school students.